Approximation of the classes W^r_β,∞ by three-harmonic Poisson integrals
In the paper, we solve one extremal problem of the theory of approximation of functional classes by linear methods. Namely, questions are investigated concerning the approximation of classes of differentiable functions by λ-methods of summation for their Fourier series, that are defined by the set Λ ={λ _δ (· )\